The Metaphysical, Epistemological, and Theological Background to Aquinas's Theory of Education in the De Magistro - MOONEY, T. Brian (Institutional Knowledge at Singapore Management University, 2014)
This article explores the relation between Aquinas’ metaphysical, epistemological and theological ideas and his theory of education as presented in the De Magistro and other writings. Aquinas’ theory of education is based on a theological metaphysics of human nature and an account of human rationality that is grounded in human nature. In the first section after the introduction we provide a synopsis of Aquinas’ metaphysical narrative, but in a contemporary key that draws upon the resources of Analytical Thomism. However, this theologically inspired metaphysics leads to a somewhat neglected epistemology that is crucial to his understanding of teaching and learning in the De Magistro – the notion of connatural knowledge that we explore in the second section. Our exposition of the Thomistic ontology of the human person together with the notion of connatural knowledge, provide the context for understanding the De Magistro in the third section.